2022
DOI: 10.1186/s10033-022-00791-4
|View full text |Cite
|
Sign up to set email alerts
|

Research Development on Fish Swimming

Abstract: Fishes have learned how to achieve outstanding swimming performance through the evolution of hundreds of millions of years, which can provide bio-inspiration for robotic fish design. The premise of designing an excellent robotic fish include fully understanding of fish locomotion mechanism and grasp of the advanced control strategy in robot domain. In this paper, the research development on fish swimming is presented, aiming to offer a reference for the later research. First, the research methods including exp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(4 citation statements)
references
References 251 publications
(235 reference statements)
0
4
0
Order By: Relevance
“…could be conducive to sustaining the Cr into Mg(Cr, Al) 2 O 4 spinel phase precipitated from slag. The research of Liu et al [6][7][8] exhibit the influence of slag composition on the dissolution of chromium ore which shows that the dissolution of chromium ore increases with the decrease of slag basicity under high basicity condition (B = 0.8-1.6). Moreover, the increase in mass fraction of Al 2 O 3 and MgO results in the reduction of chromium ore dissolution.…”
Section: Influence Of Slag Chemistry On the Dissolution Of Fecr 2 O 4...mentioning
confidence: 99%
“…could be conducive to sustaining the Cr into Mg(Cr, Al) 2 O 4 spinel phase precipitated from slag. The research of Liu et al [6][7][8] exhibit the influence of slag composition on the dissolution of chromium ore which shows that the dissolution of chromium ore increases with the decrease of slag basicity under high basicity condition (B = 0.8-1.6). Moreover, the increase in mass fraction of Al 2 O 3 and MgO results in the reduction of chromium ore dissolution.…”
Section: Influence Of Slag Chemistry On the Dissolution Of Fecr 2 O 4...mentioning
confidence: 99%
“…By combining deep reinforcement learning and fluid simulation, an energy-saving strategy was proposed, which enabled followers to save energy by using vortices in the leader’s wake [ 17 ]. More studies can be found in [ 18 ].…”
Section: Introductionmentioning
confidence: 99%
“…In the past few decades, various bionic robotic fish with BCF mode have been developed [ 11 , 12 ]. From the perspective of bioinspired design, these robots can be roughly classified into the discrete mechanism with multiple joints and the continuous compliant mechanism [ 13 , 14 ].…”
Section: Introductionmentioning
confidence: 99%